Trends in the extraction, purification, characterisation and biological activities of polysaccharides from tropical and sub-tropical fruits – A comprehensive review. (15th June 2020) - Mohan, Kannan; Muralisankar, Thirunavukkarasu; Uthayakumar, Venkatachalam; Chandirasekar, Ramachandran; Revathi, Nagarajan; Ramu Ganesan, Abirami; Velmurugan, Kalamani; Sathishkumar, Palanivel; Jayakumar, Rajarajeswaran; Seedevi, Palaniappan
Graphical abstract: Highlights: Extraction, purification and biological activities of polysaccharides from tropical and sub-tropical fruits were summarised. Structural characterisation of the fruits polysaccharides were briefly discussed. New perspectives for the future work of these polysaccharides were discussed. Abstract: Tropical and sub-tropical fruits are tremendous sources of polysaccharides (PSs), which are of great interest in the human welfare system as natural medicines, food and cosmetics. This review paper aims to highlight the recent trends in extraction (conventional and non-conventional), purification and analytic techniques of fruit polysaccharides (FPSs). The chemical structure and biological activities, such as immunomodulatory, anti-cancer, anti-oxidant, anti-inflammatory, anti-viral, anti-coagulant and anti-diabetic effects, of PSs extracted from 53 various fruits were compared and discussed. With this wide coverage, a total of 172 scientific articles were reviewed and discussed. This comprehensive survey from previous studies suggests that the FPSs are non-toxic and highly biocompatible. In addition, this review highlights that FPSs might be excellent functional foods as well as effective therapeutic drugs. Finally, the future research advances of FPSs are also described. The content of this review will promote human wellness-based food product development in the future.